Development of A Green Packaging Assessment Tool For Manufacturing Industry - Fu Haw, Ho; Saharudin, Nurul Najwa (Research Progress in Mechanical and Manufacturing Engineering, 2021)
Single-use plastics waste is one of the major problems found in developing and developed countries. This study aims to evaluate the influencing factors for next functional life performance of single-use plastics. In this study, an assessment tool which gives a performance index for the next functional life of single-use plastics was developed. This study applied Analytic Hierarchy Process (AHP)  in data collection and synthesis from the selected experts from plastics industry. Seventeen factors were generated from a questionnaire and were then ranked by priority using the AHP method. There are six participants ranged from engineer to manager level were involved in answering the questionnaire, particular in evaluating the importance level among the determined next functional factors of plastics. Next, the extracted results from AHP analysis is used to develop an assessment tool which suggests the next functional of single-use plastics. Two university experts were chosen to validate the assessment tool, and the results are found acceptable. The findings of this study could be used as a guideline for plastics industry companies in designing the green product and improve resource sustainability especially in the rethinking of plastics lifecycle performance during its end of life.